Invertebrate diversity in the intertidal zone of Lombang beaches, Sumenep, Madura according to area utilization - Vikry Nurul Iman Iman; Lise Chamisijatin; Nurul Mahmudati (LPPM Universitas Negeri Jakarta, 2025)
Pantai Lombang had experienced many human-induced environmental pressure, presently from tourist activities, which may lower the coastal biotic biodiversity, an important aspect for the livelihood of local inhabitants. Some groups of animals may directly be influenced by the activities, especially some non motile marine invertebrates which are prone to recreational activities and/or tourist accidental picking. The purpose of this study is to find the group of invertebrates in the intertidal zone and describe the diversity of invertebrates in the intertidal zone in Lombang Beach, Sumenep Regency. The research method uses belt transect at three differing stations: the tourist area, fishpond area and a least utilized area. The result showed that the invertebrates in the least utilized area are higher in diversity and evenness index compared to two other areas. The least utilized area also inhabited with more species compared to two other area. This condition may relate to the higher DO in the area, compared to two other area. This result may be important in the management of biodiversity on utilized beaches area in Indonesia.